Analysis of Service Quality, Price, and Transaction Ease on Customer Decisions Regarding Gold Pawn Products at Pegadaian Sumbawa Branch - Alan Budi Kusuma (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of service quality, price, and transaction ease on customer decisions in using the gold pawn product at the Pegadaian Sumbawa Branch. The background of this research is based on the growing public demand for fast and secure short-term financial solutions, with gold pawning emerging as one of the most popular alternatives. In this context, Pegadaian's success in attracting and retaining customers is largely determined by three main factors: service quality which includes reliability, responsiveness, assurance, empathy, and tangible evidence; competitive and transparent pricing; and transaction ease, which reflects accessibility and process efficiency. This research employs a descriptive qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis was carried out through stages of data condensation, data presentation, and drawing conclusions. The results of the study indicate that these three variables play a significant role in shaping customer perceptions and loyalty toward the gold pawn product. Responsive and empathetic service quality is the primary factor in building trust, while competitive pricing and ease of transactions provide comfort and efficiency for customers. In conclusion, the synergy between excellent service, appropriate pricing, and transaction convenience is key to enhancing customer appeal and satisfaction with the gold pawn product at the Pegadaian Sumbawa Branch. The implications of these findings can serve as a strategic reference for developing pawn services based on the needs and expectations of the local community.